Road pricing is not always green - Fosgerau, Mogens; Jensen, Thomas C. (Proceedings from the Annual Transport Conference at Aalborg University, 2010)
This paper analyses a tax reform, explicitly conceived by policy makers to be climate-friendly, that partly replaces a high vehicle registration tax by road user charging and allows for differentiation of the remaining registration tax by fuel efficiency. A tight microeconomic framework is proposed to analyze such a reform. For the case of Denmark, the analysis shows that the reform is likely to yield a significant and robust welfare gain. However, it seems not unlikely that CO2 emissions may increase as a result of the reform.